2019
DOI: 10.3390/ma12172656
|View full text |Cite
|
Sign up to set email alerts
|

Bitumen Recovery from Crude Bitumen Samples from Halfaya Oilfield by Single and Composite Solvents—Process, Parameters, and Mechanism

Abstract: Since 2007, heterogeneous, high-viscosity active bituminous formations have often occurred during the drilling process in Yadavaran oilfield (Iran), Halfaya oilfield (Iraq), and tar sands (Canada). The formation of bitumen exhibits plastic and creep properties, and its adhesion is strong, so drilling accidents are easily caused, such as adhering vibrating screen, drill pipe sticking, lost circulation, and even well abandonment. These complex problems cause huge economic losses. Solvents used to dissolve bitume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The daily gas open‐flow productivity per well of commercial gas wells in the study area is >3000 m 3 . As can be seen from Figure 15, there is a positive correlation between F C and open‐flow productivity 58,59 . Factors affecting gas well productivity are multifaceted, including geological factors and engineering factors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The daily gas open‐flow productivity per well of commercial gas wells in the study area is >3000 m 3 . As can be seen from Figure 15, there is a positive correlation between F C and open‐flow productivity 58,59 . Factors affecting gas well productivity are multifaceted, including geological factors and engineering factors.…”
Section: Discussionmentioning
confidence: 91%
“…As can be seen from Figure 15, there is a positive correlation between F C and open-flow productivity. 58,59 Factors affecting gas well productivity are multifaceted, including geological factors and engineering factors. Fracture is one of the geological factors, not the only factor.…”
Section: Relationship Between F C and Gas Well Productivitymentioning
confidence: 99%
“…3 shows the detailed experimental procedures for bitumen recovery and SARA analysis. The experimental procedure was in accordance with those in previous studies, 32,33 and the (SARA) fractionation of bitumen was performed as per ASTMD4124. 5 First, 10 g of the crude bitumen sample was mixed in 60 mL of toluene.…”
Section: Methodsmentioning
confidence: 99%
“…Studies demonstrate that band structures can be tuned effectively and conveniently according to such a strategy. In our further investigation, a phenomenon is found that the thermal-sensitive materials can own a notable viscoelasticity, which means the storage modulus of materials is strongly dependent on the frequency of wave propagation [27][28][29][30][31]. Previous research shows that the band structures of PCs are considerably influenced by frequencydependent storage modulus.…”
Section: Introductionmentioning
confidence: 91%